Educational Game: Introduction to 11 Icons in Each ASEAN Member Country - Sinambela, Ilmi Suciani; Avilla, Yudha (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
The use of games in learning media is an effective strategy in increasing children's knowledge. This provides a more immersive and enjoyable learning experience for children. This research aims to develop a simple game to introduce countries in the Southeast Asia region, especially those that are members of ASEAN, to children and the wider community through interesting visualizations. This game can be accessed easily on computer devices with low specifications so that it reaches a wider range of users. It is hoped that the creation of this simple game will provide motivation and inspiration for children and all groups to continue learning to broaden their horizons.